The Informational Content of Ex Ante Forecasts - Fair, Ray C.; Shiller, Robert J. (The Review of Economics and Statistics, 1989)
The informational content of different forecasts can be compared by regressing the actual change in a variable to be forecasted on forecasts of the change. We use the procedure in Fair and Shiller (1987) to examine the informational content of three sets of ex ant. forecasts: the American Statistical Association and National Bureau of Economic Research Survey (ASA), Data Resources Incorporated (DRI), and Wharton Economic Forecasting Associates (UEFA). We compare these forecasts to each other and to quasi ex ante forecasts generated from a vector autoregressive model, an autoregressive components model, and a large-scale structural model (the Fair model).